MENGOPERASIKAN MICROSOFT EXCEL - Citra Siahaan; Meylania Sumarauw; Revalin Gultom; Sarah Ottay; Aria Linggot; Amelia Wior; Crisela Monto; Bintang Putriana; Stevani Grasilia; Rahel Langkai (STIKES Columbia Asia Medan, 2024)
Microsoft Excel is a software that is very important in processing data, both in the world of education, business and daily needs. However, even though many people often use it, quite a few have difficulty operating some of the important features provided by Excel. Some problems that often arise include difficulties in using complex formulas, lack of understanding of basic and advanced functions, and complicated data format settings. This ignorance results in decreased user productivity, inaccurate data produced, and the time required to complete tasks becomes longer.